Emerging investigator series: preferential adsorption and coprecipitation of permafrost organic matter with poorly crystalline iron minerals - Eva Voggenreiter; Philippe Schmitt-Kopplin; ThomasArrigo, Laurel; Casey Bryce; Andreas Kappler; Prachi Joshi (My University, 2024)
Future permafrost thaw will likely lead to substantial release of greenhouse gases due to thawing of previously unavailable organic carbon (OC). Accurate predictions of this release are limited by poor knowledge of the bioavailability of mobilized OC during thaw. Organic carbon bioavailability decreases due to adsorption to, or coprecipitation with, poorly crystalline ferric iron (Fe(III)) (oxyhydr)oxide minerals but the maximum binding extent and binding selectivity of permafrost OC to these minerals is unknown. We therefore utilized water-extractable organic matter (WEOM) from soils across a permafrost thaw gradient to quantify adsorption and coprecipitation processes with poorly crystalline Fe(III) (oxyhydr)oxides. We found that the maximum adsorption capacity of WEOM from intact and partly thawed permafrost soils was similar (204 and 226 mg C g−1 ferrihydrite, respectively) but decreased to 81 mg C g−1 ferrihydrite for WEOM from the fully thawed site. In comparison, coprecipitation of WEOM from intact and partly thawed soils with Fe immobilized up to 925 and 1532 mg C g−1 Fe respectively due to formation of precipitated Fe(III)–OC phases. Analysis of the OC composition before and after adsorption/coprecipitation revealed that high molecular weight, oxygen-rich, carboxylic- and aromatic-rich OC was preferentially bound to Fe(III) minerals relative to low molecular weight, aliphatic-rich compounds which may be more bioavailable. This selective binding effect was stronger after adsorption than coprecipitation. Our results suggest that OC binding by Fe(III) (oxyhydr)oxides sharply decreases under fully thawed conditions and that small, aliphatic OC molecules that may be readily bioavailable are less protected across all thaw stages.